Unequal Care: A Case Study of Interorganizational Relations in Health CareUnequal Care: A Case Study of Interorganizational Relations in Health Care, by Milner Murray Jr. New York: Columbia University Press, 1980, 204 pp., $22.50 cloth. - Schermerhorn, John R. (Academy of Management Review, 1982)
The article reviews the book “Experiential Learning and Change: Theory, Design and Practice,” by Gordon A. Walter and Stephen E. Marks.